Validation and implementation of Aperio LV1 remote live view telepathology system for intraoperative frozen section diagnosis - Timothy Carll; Faiza Siddiqui; Meghana Agni; Rachel Poon; Cory Nash; Charlene Gettings; Nicole Cipriani (Elsevier, 2023)
Introduction: Telepathology (TP) allows for remote slide review with performance comparable to traditional light microscopy. Use of TP in the intraoperative setting allows for faster turnaround and greater user convenience by obviating the physical presence of the attending pathologist. We sought to perform a practical validation of an intraoperative TP system using the Leica Aperio LV1 scanner in tandem with Zoom teleconferencing software. Methods: A validation was performed in accordance with recommendations from CAP/ASCP, using a retrospectively identified sample of surgical pathology cases with a 1 year washout period. Only cases with frozen-final concordance were included. Validators underwent training in the operation of the instrument and conferencing interface, then reviewed the blinded slide set annotated with clinical information. Validator diagnoses were compared to original diagnoses for concordance. Results: 60 slides were chosen for inclusion. 8 validators completed the slide review, each requiring 2 h. The validation was completed in 2 weeks. Overall concordance was 96.4%. Intraobserver concordance was 97.3%. No major technical hurdles were encountered. Conclusion: Validation of the intraoperative TP system was completed rapidly and with high concordance, comparable to traditional light microscopy. Institutional teleconferencing implementation driven by the COVID pandemic facilitated ease of adoption.